Predictors of Willingness to Participate in Health Insurance Services among the Community of Jimma Town, Southwest Ethiopia - Aashagre Molla; Netsanet Fentahun (SAGE Publishing, 2014)
Health insurance schemes are increasingly recognized as tools to finance health care provision in low-income countries. The main objective of this study was to find out the awareness of and demand for health insurance and to identify those reasons that influence the demand in Jimma town, southwest Ethiopia. We conducted a community-based cross-sectional quantitative study on 741 households from December 1 to December 31, 2012. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 16. Presence of chronic illness in the family was the predictor of the willingness to take part in health insurance. Most of the participants have awareness about insurance, but they did little and/or gave unrelated explanation about health insurance. Only half of the participants (51.5%) wanted to have health insurance. Major reasons for not being willing to participate in health insurance were religious values and beliefs, ability to pay for their health-care cost, and feeling of being unable to pay the premium because of low income.